渐开线内齿轮副相对滑动率的研究 - 章易程; 李蔚; 聂昌平 (Jixie chuandong)
The relative sliding ratio formulas of an involute internal spur gear pair are developed. The influences of teeth number （transmission ratio）, module, addendum modification coefficient, center distance and so on are analyzed on the relative sliding ratio of each transmission type along the action line of.two gears.